The Incidence of Mental Disorders Increases over Time in Patients with Cancer Pain: Data from a Retrospective Cohort Study - Michael Brinkers; Giselher Pfau; Anne-Marie Toepffer; Frank Meyer; Moritz A. Kretzschmar (Pain Research and Management)
Background. It is well known that cancer patients more seldom have a psychiatric disorder than noncancer patients with chronic pain. Conversely, earlier studies have suggested that, at the psychiatric level, long-term cancer survivors (LCSs) have more in common with noncancer patients affected by chronic pain. Materials and Methods. We investigated 89 cancer patients with acute pain (Acute Cancer Pain Patients, ACPPs) treated at a university outpatient chemotherapy department and compared these with 61 LCSs (living >5 yr after the first diagnosis) admitted by general practitioners for the treatment of noncancer pain. Upon administration, each patient was psychiatrically assessed by a liaison-psychiatrist conducting a semistructured interview. In a second step, we compared the LCS patients with hitherto treated noncancer patients suffering from chronic pain and ACPPs with data published by Derogatis in 1983. Results. In a comparison of LCSs with ACPPs, LCSs have more patients with brain organic disorders and more addictions. The largest cancer group within the LCSs is patients with urogenital (Uro) cancer (44.3%), while within the ACPPs, these are patients with cancer of the gastrointestinal (GI) tract (ACPP-GI, 57.2%). As far as the distribution of mental disorders is concerned, long-term cancer survivors show some similarities to noncancer patients. The data of ACPPs are similar to those of cancer patients, published by Derogatis. Discussion. The higher values of addiction and brain organic disorders, in particular, and the slight differences for psychic disorders in general of LCSs vs. ACPPs may result from the different cancer types and a longer survival time for urogenital tract cancer compared to GI cancer. In an additional examination, we compared patients with acute cancer of the GI tract (ACPP-GI, n = 50) with those of the urogenital tract (ACPP-Uro, n = 43). ACPP-Uro had the lowest percentage of patients with psychiatric disorders in general (ACPP-Uro 37.2%, ACPP-GI 50.0%, all LCSs 65.6%, and LCS-Uro 74.1%) and addiction, in particular (ACPP-Uro 2.3%, ACPP-GI 4.0%, and LCSs 13.1%). Conclusion. Cancer patients can develop a process of chronification with an increase in the prevalence of mental disorders. For urogenital cancer, an increase in the probability to develop mental disorders is a function of time.